The Hobbit - Tolkein, J R R (London Harpercollins, 1937)
"The Hobbit," written by J.R.R. Tolkien, is a fantasy novel that follows the journey of Bilbo Baggins, a reluctant hobbit who lives a quiet life in the Shire. His life is upended when the wizard Gandalf and a group of thirteen dwarves, led by Thorin Oakenshield, arrive at his doorstep, seeking a burglar to help them reclaim their homeland and treasure from the dragon Smaug.
Keywords: Text